A Brief History of Progress on Nanotechnology: When Will the 'Magic' Nanobullet Shoot? / Renad Alyautdin - Alyautdin, Renad (Universiti Teknologi MARA Cawangan Selangor, 2018)
About a hundred years ago, chemist and biologist Paul Ehrlich introduced the concept of the "magic bullet". So he denoted his dream - a drug that when injected into the body of the patient itself will find and kill the pathogen of the disease, without causing damage to the patient. He suggested that it is possible to find a molecule that would affect a given biological object, for example, kill pathogenic microbes or cancer cells, but did not affect the human body. Such hypothetical molecules he called then "magic bullets". In the mid-sixties, the English scientist Alec Douglas Bangham, assessing the role of phospholipids in blood coagulation, studied the structure of dispersions formed by the swelling of phospholipids under condition of water excess. On electron micrographs he saw layered particles, similar to the membrane structures of a cell. The following study showed that the substances present in the solution at the time of swelling of the phospholipids are incorporated inside these particles and are retained there for a long time, exchanging with the outer solution at a very low rate. So for the first time it was established that phospholipids, which are the main components of cell membranes, are able spontaneously to form closed shells in water .